Pengembangan Game Edukasi Pada Mata Pelajaran Administrasi Sistem Jaringan Kelas XII TKJ di SMK Muhammadiyah 1 Padang - Hermawan, Firdaus; Irsyadunas; Novita, Rini (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This research is based on the problem, namely that students find it difficult to understand the material presented by the teacher in class because the media used by the teacher in delivering the material seems boring and makes students sleepy during the learning process. Many students' learning outcomes have not yet reached the KKM and the level of student activity is still categorized as low. The aim of this research is to develop educational game media on the subject of Network Systems Administration. The subjects of this research were 15 students as samples. Data collection techniques using a questionnaire with a Likert scale. At the testing stage, Alpha testing is used, namely media expert validity testing and material expert validity testing, as well as Beta testing, namely teacher practicality testing and student practicality testing. The research results show that the level of validity of educational game media obtained a value of 0.82 in the valid category, while the validity of the material obtained a value of 0.87 in the valid category. The teacher's practicality level scored 85.83% in the very practical category and students' practicality scored 87.85% in the very practical category. Based on this data, it can be concluded that this educational game media is suitable for use in the learning process at SMK Muhammadiyah 1 Padang. The results of this research are recommended for teachers of Network Systems Administration subjects as a learning medium.